Electronic Imaging & the Visual Arts. EVA 2015 Florence 13-14 May 2015 - Cappellini, Vito (Proceedings e report, 2015)
Information Technologies of interest for Culture Heritage are presented: multimedia systems, data-bases, data protection, access to digital content, Virtual Galleries. Particular reference is reserved to digital images (Electronic Imaging & the Visual Arts), regarding Cultural Institutions (Museums, Libraries, Palace - Monuments, Archaeological Sites). The International Conference includes the following Sessions: Strategic Issues; New Technologies & Applications; New 2D-3D Technical Developments & Applications; Virtual Galleries - Museums and Related Initiatives; Access to the Culture Information. Two Workshops regard: International Cooperation; Innovation and Enterprise.